Neutrophil count in the gingival wound healing process after apitoxin gel application (gingival wound healing model on Wistar rats) - Urfa Tabtila; Swastiana Eka Yunita; Muhammad Nabil Pratama; Juni Handajani (Majalah Kedokteran Gigi Indonesia, 2020)
Periodontal disease has a high prevalence in Indonesia. Gingival disease is a periodontal disease if it is severe, requires surgical therapy called a gingivectomy. Surgical periodontal procedures lead to a gingival wound that is usually treatedusing a periodontal pack. Periodontal pack has no curative property in general but assists in a wound healing process by protecting tissues. Neutrophils are inflammatory cells that act as a host’s first defense against infectious pathogens and they are important in wound healing. Wound healing can be accelerated by apitoxin gel from honeybee Apis mellifera species. The aim of this study was to determine the effectiveness of apitoxin gel on neutrophil count on gingival woundhealing process. Medical bee venom powder (Umea, Sweden) was mixed with double-distilled water to prepare a concentration of 0.01% bee venom. The solution was mixed with 10% propylene glycol, 0.01% methylparaben, and3% CMC-sodium. Thirty six gingiva of 3 month-old male Wistar rats (weighing 200-250 gram) were injured using punch biopsy (3 mm in diameter). They were treated in 4 groups: apitoxin gel, apitoxin gel with a periodontal pack, NSAIDsFlamar® gel with periodontal pack, and a periodontal pack. Three Wistar rats from each group were euthanized and their jaws were taken after 48 hours treatment to make histology slides with Hematoxylin Eosin (HE) staining. Neutrophil counts were observed. The data were analyzed using Anova test with 95% confidence level. The results showed there were significan defferebces among 4 groups (p<0.05). The highest neutrophil count on the 2nd day was found in the apitoxin gel induced the 2 day of gingival wound healing process.